Changes in Serum Prealbumin and Incision Complications Following Spinal Tuberculosis Surgery: A Preliminary Study - Yu‐cheng Bao; Ming Yu; Liang Tang; Hua‐ying Ning; Wen‐long Zhang (Orthopaedic Surgery, 2021)
Objectives To explore the trend of changes in the serum prealbumin (PA) level in patients with spinal tuberculosis during the perioperative period and its relationship with postoperative incision complications. Methods A retrospective study was performed by enrolling 162 patients (82 men and 80 women) with spinal tuberculosis who had been admitted to the Tianjin Haihe Hospital from June 2013 to June 2017. The included patients were then assigned to the elderly group (≥65 years of age, n = 35) and the non‐elderly group (<65 years of age, n = 127). The chemotherapy regimen was 3HREZ/9HRE, in combination with nutritional support for 3–4 weeks, as well as one‐stage debridement and (or) bone graft fusion and internal fixation. The serum PA levels of patients with spinal tuberculosis at admission, prior to surgery, and at 2 and 4 weeks after surgery were collected, and incision healing and sinus formation were observed for 3 months. Changes in serum PA levels of all patients at different time points were observed using one‐way analysis of variance. Pairwise comparison at different time points was performed using the least significant difference method and comparison of serum PA levels between different groups at the same time points was subjected to t‐test. The χ2‐test was used for comparison of the incidence of incision complications between different groups and between different subgroups based on different PA levels. Results There was a gradual increased trend in the PA level from admission to 4 weeks after surgery in all patients [(0.14 ± 0.03) g/L < (0.16 ± 0.04)g/L < (0.22 ± 0.04) g/L < (0.25 ± 0.04) g/L]. The increase in the non‐elderly group was higher than that in the elderly group (P < 0.01). Furthermore, the incidence of incision complications in the elderly group was higher than in the non‐elderly group (14.29% > 1.78%, P < 0.01). The serum PA level was graded in accordance with NRS2002. There were 88 patients with preoperative grade 0–1 serum PA level (≥0.16g/L) who had no incision complications. The incidence of incision complications in patients with grade 3 serum PA level (<0.10 g/L, 9 patients) was higher than in patients with grade 2 (0.100–0.159 g/L, 66 patients) (44.44% > 6.06%, P < 0.01). Conclusion Changes in serum PA level in patients with spinal tuberculosis during the perioperative period are consistent with the trend of inflammation control and nutrition improvement, and are correlated with the incidence of incision complications after surgery. The relationship between the changes and the timing of surgery is worthy of future research.